Birds - Flach, Tim; Prum, Richard O.; Prum, Richard O. ([New York] : Abrams, in association with Blackwell & Ruth, 2021)
Radiating grace, intelligence, and humor, and always in motion, birds tantalize the human imagination. Working for years in his studio and the field, Tim Flach has portrayed nature's most exquisite creatures alertly at rest or dramatically in flight, capturing intricate feather patterns and subtle coloration invisible to the naked eye. From familiar friends to marvelous rarities, Flach's birds convey the beauty and wonder of the natural world. Here are all manner of songbirds, parrots, and birds of paradise; birds of prey, water birds, and theatrical domestic breeds. The brilliant ornithologist Richard O. Prum is our guide to this magical kingdom.--
kunstcatalogus
Keywords: Flach, Tim